Naringenin Decreases Retroperitoneal Adiposity and Improves Metabolic Parameters in a Rat Model of Western Diet-Induced Obesity - Gabriela López-Almada; J. Abraham Domínguez-Avila; Rosario Maribel Robles-Sánchez; Jonathan Arauz-Cabrera; Gustavo Martínez-Coronilla; Gustavo A. González-Aguilar; Norma Julieta Salazar-López (Metabolites)
Background: Obesity is a multifactorial disease with detrimental effects on health and quality of life; unregulated satiety plays a crucial role in food intake and obesity development. Naringenin (NAR) has shown beneficial effects on lipid and carbohydrate metabolism, although its impact on adiposity and satiety remains unclear. This study reports a Western diet (WD)-induced obesity model in rats, wherein 100 mg/kg of NAR was administered as an anti-obesity agent for 8 weeks; oxidative stress, lipid profile, and satiety biomarkers were then studied, as well as in silico interaction between NAR and cholecystokinin (CCK) and ghrelin receptors. Results: NAR supplementation resulted in a significant decrease in retroperitoneal adipose tissue and liver weight, as compared to the untreated WD group (p < 0.05), potentially associated with a decreased feed efficiency. NAR also inhibited the development of dyslipidemia, particularly by reducing serum triglycerides (p < 0.05). NAR supplementation increased CCK serum levels in the basal diet group, an effect that was abolished by the WD (p < 0.05); likewise, no changes were determined on ghrelin (p > 0.05). In silico data shows that NAR is capable of interacting with the CCK and ghrelin receptors, which suggests a potential for it to modulate hunger/satiety signaling by interacting with them. Conclusions: We conclude that NAR has anti-obesogenic effects and may regulate CCK serum levels, although further research is still needed.